Obstacles And Challenges In Implementing The Independent Curriculum At Sekolah Dasar Negeri (SDN) 019 Bengalon - Kurniawan, Muhammad Yahya Nuzuul; Sugianor, Sugianor; Pandiangan, Anjani Putri Belawati (Tinta Emas Publisher, 2024)
The education curriculum must be adapted to the needs and characteristics of students as it is created because it is constantly changing. To implement an independent curriculum, there are many challenges. One of them is predicting what will happen in the future and determining the best strategy to teach students at the primary level. So, this research has the aim of identifying the challenges and obstacles of implementing the independent curriculum at SDN 019 Bengalon school. The method used in this research is a qualitative method, which describes the subject about the situation and the data obtained during observation and questioning. The results of this study indicate that the implementation of the curriculum at SDN 019 Bengalon school has been carried out optimally and is ongoing, although in its implementation there are still many shortcomings The obstacles and challenges that occur in the implementation of the independent curriculum are the inefficient time for teachers to master technology. The key to the success of the implementation of the curriculum in the driving school is that the principal and his teachers must have the willingness to make changes. The principal as the leader must be able to change the mindset of the Human Resources in the school to want to make changes so that the independent curriculum can be implemented.